Safety Procedure for Biosafety and Controlling a Communicable Disease: Streptococcus Suis - Tandio, Deasy Ayuningtyas; Manuaba, Ida Bagus Amertha Putra (BALI MEDICAL JOURNAL, 2016)
Background: Streptococcus suis infection is a zoonotic disease which cause fatal outbreak. Infection  case is related to animal handling and dry season. Health workers on Timor island need to understand  more about biosafety procedure and increase awareness of the disease as a potential causes of  meningitis. Objective: To provide a simple yet comprehensive reading material for the health workers  that is exposed to meningitis. Method: This is a descriptive explorative study, to search about  Streptococcus suis in the James Cook University OneSearch library search engine and biosafety  procedure in WHO and CDC database. The information in accessed articles were compiled into a review  piece. Conclusion: The biggest risk factor for a Streptococcus suis outbreak is inappropriate pig carcass  handling. The cocci infect via micro-lesion on the handler skin. Public awareness about an appropriate  way to handle meat needed to be raised. Suspected case need to be referred to the nearest centre with  an ability to conduct a PCR test. It is essential that people, especially health workers understand that  the principles of biosafety cover the basics of the containment system, including the practice, and the  correct laboratory techniques, safety equipment, laboratory facilities to protect workers, the  environment, and the public from exposure to infectious microorganisms.
Keywords: Streptococcus suis, meningitis, pork handling